Increased Tuberculosis Reactivation Risk in Patients Receiving Immune Checkpoint Inhibitor-Based Therapy - Hsing-Wu Chen; Yao-Wen Kuo; Chung‐Yu Chen; Chin-Hao Chang; Sumei Wang; Ying‐Chun Chien; Wei‐Chen Lu; Jo‐Pai Chen; Cheng‐Yu Chang; Yu‐Feng Wei; Shih‐Chieh Chang; Chin‐Chung Shu; et al. (2024)
Abstract Objective Reports of tuberculosis (TB) during anticancer treatment with immune checkpoint inhibitors (ICIs) are increasing. However, it is not clear whether the use of ICIs is a significant risk factor for TB, including reactivation or latent TB infection (LTBI). Methods To determine the risk of TB reactivation in patients with lung cancer who use ICIs or tyrosine kinase inhibitors (TKIs), we conducted a retrospective study using a hospital-based cancer registry. In addition, we monitored patients with cancer using ICI or TKI in a multicenter prospective study to check the incidence of LTBI. Results In the retrospective study, several demographic factors were imbalanced between the ICI and TKI groups: the ICI group was younger, had more males, exhibited more squamous cell carcinoma in histology rather than adenocarcinoma, had fewer EGFR mutations, and received more chemotherapy. Propensity score matching was used to control for confounding factors, and we found that the incidence of TB was higher among patients with lung cancer who received ICIs than among those who received TKIs (2298 vs 412 per 100 000 person-years, P = .0165). Through multivariable analysis, group (ICI vs TKI) was the independent risk factor for TB development (adjusted hazard ratio (aHR): 6.29, 95% CI, 1.23-32.09, P = .0269). In the prospective cohort, which included 72 patients receiving ICIs and 50 receiving TKIs, we found that the incidence of positive seroconversion of LTBI by interferon gamma release assay (IGRA) was significantly higher in patients receiving ICIs (18% vs 0%, aHR: 9.88, P = 0.035) under multivariable Cox regression. Conclusion The use of ICIs may be linked to a higher likelihood of TB reactivation and LTBI than individuals solely receiving TKIs as anticancer therapy. Consequently, the implementation of a screening program for TB reactivation and LTBI among patients undergoing ICI treatment could prove advantageous by enabling early detection and prompt treatment of the infection.